Efeito de uma intervenção breve com o uso de jogo virtual em idosos longevos - Valduga, Luana Vieira Alves (2018)
In recent years, the population of elderly people has gained prominence in terms of representative growth. With the aging, a good part of the elderly present a decline in their functions, which reduces the functional capacity and makes the elderly fragile, especially by the reduction of strength that reduces balance and brings risks to maintain the independence of the elderly. The intervention performed in the elderly should be done not only playful but also pleasurable to minimize complications to encourage adherence to interventions. Virtual games have been used for interventions in this public, however they are not produced for this purpose. New games have been created and applied to the elderly to meet their needs. The objective of the present study was to identify the effect of a brief intervention with the use of a virtual game in elderly people. This is a quasi-experimental study carried out at the Cardiology Institute of the Federal District, in Taguatinga-DF, and in the Laboratory of Physical Evaluation and Training of the Catholic University of Brasília, from October to December 2017. The research evaluated the capacity (TUG) and 5-fold sit-up test (TSL5X), measured strength using the isokinetic dynamometer and also assessed fragility by means of the fragility phenotype in a sample composed of elderly individuals who were older than program. The sample was composed at the end by 10 participants who finished the 10 sessions, with a mean age of 83.5 years. There was no difference between the pre and post-intervention moments in the comparative analysis of measures related to functional capacity, TUG, Sit and lift test 5 repetitions and knee extensor strength test (p> 0.05), however, the evaluation of muscle strength of the knee extensors presented a mean variation of 14% increment in the MID and 11% in the SEM in 7 volunteers. There was improvement in the classification of risk of falls where 6 participants obtained a reduction in TUG time. In the sit-up and sit-up test 5 repetitions there was an 8% increase in participants' performance. Regarding the fragility, there was no change in the classification of the fragility phenotype. It is concluded, therefore, that the use of virtual play as an intervention strategy has positive effects on muscular strength and functional capacity in the elderly.